Download as pdf or txt
Download as pdf or txt
You are on page 1of 4

This is what I mean, Roos.

We are adding numbers, forming the sequence:

a1 = 6 (your choice)
a2 = 12 (my choice)
a3 = a1 + a2 = 6 + 12 = 18
a4 = a2 + a3 = 12 + 18 = 30

For any positive whole number n ∈ N greater or equal than 3, we have that
an = an-2 + an-1 ,
which is the same as saying that for all positive numbers n ∈ N, it is
an+2 = an + an+1 .
This means that the next number in the sequence depends in the previous two. We call this formula a
recursive formula. Recursive formulas are difficult to compute by hand, and we wish to have an
explicit formula to express an in terms of n, rather than in terms of an-1 and an-2 .

To get a feel about how powerful are explicit formulas that are not recursive, consider the following
example:

We can define this sequence:


b 1 = 1,
bn = bn-1 + n.

How do we know b30 without having to compute b29 , b28 ,... ?

n( n + 1 )
The answer is that there is a formula that one can find, and it turns out that bn = . Thus, it is
2
30 · 31
really easy to compute = 15 · 31 = 310 + 155 = 465. We avoid the sum
2
1 + 2 + 3 + 4 + 5 + 6 + ... +29 + 30.
We will not go into detail about why is true, unless you ask for it. The proof is really pretty and simple,
but a deviation from the main topic.

It is not hard to see that the choice of a1 and a2 determines the whole sequence. We will see in a
moment why this is true.
The primordial example of this kind of sequence is the one by Fibonacci:
F1 = 1, F2 = 1

so that F3 = 2, F4 = 3, F5 = 5, F6 = 8, ...

Now, this sequence will appear in the explicit formula that we will construct.

Let us get started in the task of finding a general formula for a generic sequence of the form

a1 and a2 known, subject to the relation an+2 = an+1 + an .

We compute the first few terms:


a1 = a1
a2 = a2
a3 = a2 + a1
a4 = a3 + a2 = (a2 + a1 ) + a2 = 2a2 + a1
a5 = a4 + a3 = (2a2 + a1 ) + (a2 + a1 ) = 3a2 + 2a1
a6 = a5 + a4 = (3a2 + 2a1 ) + (2a2 + a1 ) = 5a2 + 3a1
a7 = a6 + a5 = (5a2 + 3a1 ) + (3a2 + 2a1 ) = 8a2 + 5a1 .

Do you see a pattern here?


First, we can clearly see that we can express everything using instances of the first two terms, a1 and
a2 .
But the most important thing here is, indeed, the Fibonacci numbers appear in the coefficients of a2
and a1 (!)

It is easy to see that an = Fn-1 a2 + Fn-2 a1 . One can verify this formally using mathematical induction
(I tried teaching you what it was, but it is a bit dull and unmotivated the first time you get exposure to
it).

And, good news, there is already an explicit formula for Fn , which is called Binet's formula. Although,
it is not really practical, because it looks like this:
n n
5 5
1+ 2
- 1- 2
Fn = .
5

It is surprising that this formula about whole numbers involves really "complicated decimal numbers"
such as 5.

You might also like